Pengaruh Transparansi dan Akuntabilitas Pengelolaan Keuangan Desa Terhadap Perubahan Aset Desa : (Studi Kasus Desa Sumurgayam Kecamatan Paciran Kabupaten Lamongan) - Wahid Suyoto, Agus; Rosidah, Anita (BULLET : Jurnal Multidisiplin Ilmu, 2023)
One of the obstacles that occurs in village government is the lack of control over village funds obtained from the Village Fund Allocation. This research aims to determine the effect of transparency and accountability in village financial management on changes in village assets. Researchers conducted research in Sumurgayam Village, Paciran District, Lamongan Regency. The method in this research uses quantitative descriptive methods. The population in this research is the people of Sumurgayam Village. The results show that the Transparency Variable and Accountability Variable both influence each other's village assets.